Cardiovascular risks in type 2 diabetes and the interpretation of cardiovascular outcome trials - Hinnen D (Dove Medical Press, 2019)
Deborah Hinnen,1 Davida F Kruger2 1Department of Health and Wellness, Memorial Hospital Diabetes Center, University of Colorado Health, Colorado Springs, CO 80909, USA; 2Henry Ford Health System, Division of Endocrinology, Diabetes, Bone and Mineral Disease, Henry Ford Medical Center – New Center One, Detroit, MI 48202, USA Background: Patients with type 2 diabetes (T2D) are at increased cardiovascular (CV) risk compared to subjects without diabetes, with some data estimating that CV disease (CVD) risk is doubled in these individuals. Additionally, CVD remains the leading cause of death in patients with T2D, so it is paramount to determine the relationship between these two diseases. Purpose: Older diabetes treatments have limited CV safety data. In 2008, the US Food and Drug Administration published guidance for manufacturers on antihyperglycemic agents, requiring studies to ensure CV safety of new therapies. Since then, manufacturers of many newer agents have conducted and published results from CV outcomes trials (CVOTs), with more trials due to publish soon. This review discusses the relationship between CVD and T2D and explores findings from the latest CVOTs of glucose-lowering agents to guide nurse practitioners in their prescribing patterns for patients with T2D. Conclusion: Patients with T2D are at high risk of CVD, so CV risk should be carefully considered when managing these patients, and CV risks and benefits of antidiabetic drugs should be included in prescribing decisions. Keywords: cardiovascular disease, chronic disease management, type 2 diabetes mellitus, nurse practitioners